APLIKASI FOSFAT PADA PROSES EKSTRAKSI TEH HIJAU UNTUK MINUMAN TEH HIJAU SIAP MINUM - Rima Hidayati; Nuri Andarwulan; Dian Herawati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Color is one of quality parameters that affects consumer intention to purchase ready to drink (RTD) green tea. Consumers expect RTD green tea to have yellow greenish color, however the color becomes brown and darker during the shelf life. This study aimed to evaluate the effect of phosphate mix addition to water prior to green tea leaves extraction on pH, color, and the tannin in tea extract, pre-RTD, and RTD during incubation period at 60°C for 2 days. The pre-RTD contained tea extract, sugar, and ascorbic acid. Addition of sodium bicarbonate was done in pre-RTD to obtain RTD with pH of 6.1±0.2. The type of phos-phate used was sodium acid pyrophosphate (SAPP) and phosphoric acid. The concentrations of SAPP were 650 and 1300 mg/L, while those of phosphoric acid were 125, 250, and 500 mg/L.The total phospho-rous added from the combination of SAPP and phosphoric acid was 221-521 mg/L. Meanwhile, green tea extracted without phosphate was used as a control. The results showed that phosphate addition to water prior to green tea extraction caused decrease in pH of tea extract from 5.83±0.18 to 2.8-3.8, decrease in browning intensity, and reduced tannin degradation during the incubation period. Sugar and ascorbic acid added to the tea extract resulted in pH in all samples <4.0 and maintained the lightness of the pre-RTD. Phosphate application was not able to retain the color of RTD after incubation period. This study showed that addition of phosphorous as a combination of SAPP and phosphoric acid to water at concentrations of 221-521 mg/L prior to green tea extraction had positive impact in reducing browning intensity of RTD green tea with pH of lower than 4.0.